Maximum Power Point Determination of Bifacial PV Using Multi-Verse Optimization Algorithm Applied on Different Cell Models - Angela Najdoska and Goga Cvetkovski (Sciendo, Warsaw, Poland, 2025)
In the design process of a photovoltaic (PV) power plant the determination of the maximum power that can be extracted from the PV modules in a plant is essential, especially for the dimensioning of the individual parts of the plant. This paper presents the determination of the maximum power point of a bifacial photovoltaic system using three different cell models. The optimal power point is determined by using a novel multi-verse optimization algorithm (MVO), as an optimization tool. In this research work the maximum power point of bifacial photovoltaic modules is determined by using the following three photovoltaic cell models such as: ideal single diode model, real single diode model and two diode model of photovoltaic cell. The above-mentioned cell models are developed for single sided PV mod-ules and therefore a proper modification of those models is necessary in order to be applied for the investigated modules. The purpose of this optimization procedure is to determine the maximum power of a bifacial PV module by minimising the power difference between the calculated power and the experimentally determined power for certain atmospheric conditions.
Keywords: maximum power point, PV cell, bifacial module, multi-verse optimization algorithm, PV cell equivalent circuit